A comprehensive assessment of travel motivations and constraints faced by solo female travelers visiting tourism destinations of Kashmir and Ladakh Region - Sadakat Akram; Rukhsana Majeed; Javed Iqbal (Journal of Rural Tourism, 2025)
Purpose - This research explores the motivations and constraints of solo female travelers in Kashmir and Ladakh, focusing on their pursuit of independence and personal freedom while addressing social and cultural challenges. It also examines how these factors influence their destination choices.Methodology - A quantitative approach was used, with surveys distributed to 275 solo female tourists in popular Kashmir and Ladakh destinations. Data was analyzed using SPSS version 25.0.Findings - Solo female travelers are primarily motivated by independence, self-improvement, and unique experiences. Psychological factors such as escaping daily routines and boosting confidence were key, while sociocultural constraints like gender norms and family disapproval hinder independent travel.Originality - This study fills a gap in existing literature by focusing on solo female travelers in Kashmir and Ladakh. It offers valuable insights for tourism stakeholders to enhance the experiences of this emerging group and suggests strategies to boost female solo travelers' confidence and engagement.